Stabilizing Lithium-Sulfur Cells with Practical Loading and Cycling Conditions Using Li2S8-Containing Ethereal Electrolyte Solution. Issue 14 (11th November 2020) - Markevich, E.; Salitra, G.; Yoshida, H.; Sawada, S.; Aurbach, D.
Abstract : We report on stabilization of Li–S cells cycled with an areal charge/discharge capacity of 2 mAh cm −2 at current densities of 1–2 mA cm −2 using ethereal LiTFSI/LiNO3 /DOL/DME electrolyte solution containing 0.1M Li2 S8 . This electrolyte solution enables stable lithium metal stripping−plating both in symmetric Li∣Li and full Li–S cells with composite binder free sulfur impregnated activated carbon fibers cathodes. The addition of Li2 S8 substantially extends cycling life of these cells due to the formation of smooth non-dendritic Li metal surface protected with an effective SEI enriched with Li sulfides, sulfites and sulfates species. Symmetric Li∣Li could be cycled stably for more than 1000 h at 1–2 mA cm −2 with Li2 S8 -containing electrolyte solutions. Full Li–S cells demonstrate more than 500 stable cycles (at least 3 times more than with Li2 S8 free electrolyte solution) at a current density of 1 mA cm −2 and an areal capacity of 2 mAh cm −2 . The most stable cycling results were achieved for the cells cycled with discharge cut off voltage of 1.9 V preventing the depletion of LiNO3 . The use of electrolyte solutions containing liquid lithium poly-sulfides makes possible considerable decrease in the amount of the electrolyte solution and increases the energy density of the cells.